Innovative theory in the digital age: Clarifying our positions. (March 2023) - Grover, Varun; Lyytinen, Kalle
In this paper, we respond to Baiyere, Berente and Avital (2023) who misinterpret portions of our article. In this essay, we engage in a dialog with these authors and clarify our positions and even reinforce some points the authors themselves are making.